Perbandingan Hak Asasi Manusia Menurut Undang Undang Dasar 1945 Dengan Undang-Undang No.39 Tahun 1999 Tentang Hak Asasi Manusia - Azmi Syahputra (PRANATA HUKUM, 2011)
The Comparison of Human Rights in Indonesian Constitution Year 1945 with Human Rights Law No.39/1999, Human Rights in Indonesia already exists in the Indonesian Constitution Year 1945 (original manuscript) long before the formulated in the international legal instrument. In the reform regime, which one way is to amended the Indonesia Constitution Year 1945. Amended constitution have been accommodated human rights, not only the basic norms as contained in several articles in Universal Declaration of Human Rights, but also incorporated norms of Human Rights Obligations, this can be seen from Article 28 A up to 28 J of the Indonesia Constitution. Moreover, Human Rights Law No. 3911999 to legimimized of independent institutions (Human Rights Commission). Law Enforcement of human rights in Indonesia are still very apprehensive, even many cases unresolved.